Analisis Kepatuhan Antenatal Care (Anc) Terhadap Kejadian Komplikasi Kehamilan Di Puskesmas Tiudan Kecamatan Gondang Kabupaten Tulungagung - Agustian Dwi Mahendra; Nur Yeny Hidajaturrokhmah; Suci Anggraeni (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2019)
Introduction: Pregnant women for antenatal care are very important because they can reduce the number of pregnancy complications. However, the prevalence of pregnant women to undertake Antenatal Care is very low. Objective: The purpose of this study is to analyze the Antenatal Care (ANC) approval for consideration complications in the Tiudan Health Center, Gondang District, Tulungagung District. Design: The design of this study was observational with a cross sectional design. The population in this study were all pregnant women in Tiudan Health Center, Gondang District, Tulungagung Regency, with 45 respondents. Samples were taken by purposive sampling taken 30 respondents. The data collected was processed using the chi square statistical test with significance α = 0.05. Results: The results showed that of the 30 respondents, the majority of respondents had compliant ANC contributions, namely 19 respondents (63.3%) and the majority of respondents did not experience difficulties during pregnancy, namely 22 respondents (73.3%).The results of this study were the Antenatal Care (ANC) meeting on the incidence of complications assessment in the Tiudan Health Center, Gondang District, Tulungagung District (p-value = 0.002) with the chi square test. Conclusion: Compliance of pregnant women to perform antenatal care is very important because it can help reduce pregnancy complications that can increase maternal and infant mortality